Green BIM : successful sustainable design with building information modeling - Krygiel, Eddy, 1972- (Serious skills., 2008)
"Meet the challenge of integrating Building Information Modeling and sustainability with this guide, which pairs these two revolutionary movements to create environmentally friendly design through a streamlined process. Written by an award-winning team that has gone beyond theory to lead the implementation of Green BIM projects, this comprehensive reference features practical strategies, techniques, and real-world expertise so that you can create sustainable BIM projects, no matter what their scale. From basic concepts, to sophisticated test methodologies, to improved workflows, this timely book offers a wealth of information you can implement right away."--BOOK JACKET.